Efektivitas Kepemimpinan Ketua RW 10 di kelurahan Jati Padang - Lutfi, Ahmad; Putri, Nabilah Azahra; Fitriani, Aulia Annisa; Nelsi, Yurike Shizuka (Inovan Publisher, 2024)
This study aims to determine the leadership style of the head of RW 10 in Jati Village, Padang City in increasing employee motivation and performance and to find out the obstacles in increasing employee motivation and performance. The leadership style applied by the Head of RW 10 is not only limited to leading but also as motivation and greatly affects employee performance. In a community institution, of course, the leader has a big responsibility, especially in terms of providing motivation and direction to employees. In applying his leadership style, of course, a leader must be responsible for all decisions made, and also be responsible for employee performance. This research uses qualitative research. The results showed that the leadership style in employee performance in RW 10 of Jati village has made many changes to its employees such as improving employee performance. However, there are various obstacles in implementing this decision, one of which is the lack of communication between the RW head and his subordinates so that the directions given to residents are confusing and not in line with what the RW head of Jati village said.